Measurement of azimuthal anisotropy of muons from charm and bottom hadrons in pp collisions at √s=13 TeV with the ATLAS detector - Aad, Georges; Andrei, George Victor; Bolz, Arthur; Dunford, Monica; Franchino, Silvia; Helary, Louis; Klassen, Martin; Krishnan, Anjali; Kugel, Andreas; Napolitano, Fabrizio; Ott, Philipp; Schöning, André; et al. (Physical review letters, 2020)
The elliptic flow of muons from the decay of charm and bottom hadrons is measured in pp collisions at √s=13 TeV using a data sample with an integrated luminosity of 150 pb−1 recorded by the ATLAS detector at the LHC. The muons from heavy-flavor decay are separated from light-hadron decay muons using momentum imbalance between the tracking and muon spectrometers. The heavy-flavor decay muons are further separated into those from charm decay and those from bottom decay using the distance-of-closest-approach to the collision vertex. The measurement is performed for muons in the transverse momentum range 4-7 GeV and pseudorapidity range |η|<2.4. A significant nonzero elliptic anisotropy coefficient v2 is observed for muons from charm decays, while the v2 value for muons from bottom decays is consistent with zero within uncertainties.